Emergency Considerations for Beef Cattle - Max Irsik; Todd Thrift (EDIS, 2008)
VM-167, a 5-page illustrated guide by Max Irsik and Todd Thrift, provides a general overview of beef cattle handling, care, and health concerns which may be associated with a natural disaster such as a hurricane. Includes references. Published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2008.